Regulatory T cells. - Thompson, C; Powrie, F (2004)
Regulatory T (TR) cells are a subset of T cells that function to control immune responses. Different populations of TR cells have been described, including thymically derived CD4(+)CD25+ TR cells and Tr1 cells induced in the periphery through exposure to antigen. A transcription factor, Foxp3, has been identified that is essential for CD4(+)CD25+ TR cell development and function. There is now evidence that transforming growth factor-beta might play a role in this pathway. CD4(+)CD25+ TR cells proliferate extensively in vivo in an antigen-specific manner, and can respond to both self and foreign peptides. By suppressing excessive immune responses, TR cells play a key role in the maintenance of self-tolerance, thus preventing autoimmune disease, as well as inhibiting harmful inflammatory diseases such as asthma and inflammatory bowel disease.